2000
DOI: 10.1523/jneurosci.20-23-08771.2000
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in Neurotransmitter Release Probability among Competing Inputs during Neuromuscular Synapse Elimination

Abstract: Competition among the several motor axons transiently innervating neonatal muscle fibers results in an increasing disparity in the quantal content and synaptic territory of each competitor, culminating in the permanent loss of all but one axon from neuromuscular junctions. We asked whether differences in the probability of neurotransmitter release also contribute to the increasing disparity in quantal content among competing inputs, and when in the process of competition changes in release probability become a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…At P3, mouse pups, like rats (Westerga and Gramsberger, 1990), exhibit minimal ability to crawl effectively on a smooth surface, while they can support their weight against gravity and walk with alternating hindlimb stepping by P10 -11 (Jiang et al, 1999). Furthermore, the polyneuronal innervation that characterizes neuromuscular organization in newborn mice is gradually lost and disappears by the end of the second week of life (Brown et al, 1967;Kopp et al, 2000). The relatively stable topology of lumbosacral MNs seems curiously at odds with this marked maturation of neuromuscular and functional organization.…”
Section: Resultsmentioning
confidence: 99%
“…At P3, mouse pups, like rats (Westerga and Gramsberger, 1990), exhibit minimal ability to crawl effectively on a smooth surface, while they can support their weight against gravity and walk with alternating hindlimb stepping by P10 -11 (Jiang et al, 1999). Furthermore, the polyneuronal innervation that characterizes neuromuscular organization in newborn mice is gradually lost and disappears by the end of the second week of life (Brown et al, 1967;Kopp et al, 2000). The relatively stable topology of lumbosacral MNs seems curiously at odds with this marked maturation of neuromuscular and functional organization.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular recording from soleus skeletal muscle fibers was performed by using glass microelectrodes filled with 3 M KCl (50-70 MÙ resistance) as described (28,43); see SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of multiply and singly innervated neuromuscular junctions was determined by using intracellular recording from muscle fibers in an in vitro soleus nerve-muscle preparation in which the soleus nerve was split into two bundles and each placed into a different suction electrode (28). For each impaled muscle fiber, the nerve bundle in each suction electrode was stimulated at the lowest threshold for recording the end plate potential (epp).…”
Section: Precocious Time Course Of Neuromuscular Synapse Elimination Inmentioning
confidence: 99%
“…This can be seen during development and re-innervation of muscle when individual fibers receive transient innervation from two or more motoneurons (Wyatt and Balice-Gordon, 2003). Differences emerge in the strength of convergent inputs during the subsequent loss of the polyneuronal innervation of the muscle cell, and a role for activity-dependent retrograde modulation of synaptic strength in this process has been postulated (Colman et al, 1997;Kopp et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Lo and Poo (1991), for example, induced sustained depression of transmitter release from a neuron synapsing with a cultured myocyte by delivering a train of electrical stimuli to a different neuron coinnervating the same postsynaptic cell. It has been suggested that Hebbian depression at the immature neuromuscular junction, which leads to suppression of transmitter release from less active synaptic inputs, may contribute to the disparity in transmitter release from competing inputs that is observed during synaptic elimination (Colman et al, 1997;Kopp et al, 2000).…”
Section: Introductionmentioning
confidence: 99%